On some new quantum trapezoid-type inequalities for q-differentiable coordinated convex functions - Fongchan Wannalookkhee; Kamsing Nonlaopon; Mehmet Zeki Sarikaya; Hüseyin Budak; Muhammad Aamir Ali (Journal of Inequalities and Applications, 2023)
Abstract In this paper, we establish several new inequalities for q-differentiable coordinated convex functions that are related to the right side of Hermite–Hadamard inequalities for coordinated convex functions. We also show that the inequalities proved in this paper generalize the results given in earlier works. Moreover, we give some examples in order to demonstrate our main results.